Umiranje v očeh študentov zdravstvene nege - Zgaga, Ana (Obzornik zdravstvene nege, 2004)
The introductory part of the article describes social aspect of death. The process of dying is removed from domestic environment and more and more peopleare dying in hospitals and other institutions. Nurses often have to dealwith dying patients, who have special nursing needs. Consequently, nurses can suffer from severe stress when taking care of dying patients. There is a problem because in the study program of nursing care there are very few hours of lessons intended to nursing care of dying patients. The second part presents the results of a questionnaire conducted among the second and third year (regular) nursing students at the Ljubljana University. 128 students nursing took part in the research, where qualitative and quantitative processing of data was used. Students of nursing are aware that at the end of the study their knowledge about palliative care will be insufficient. Comparison showed that students have different ethical opinion about nursing care of dying patients that employed nurses. Qualitative analysis of the results showed that students although they are young, still tend to take in consideration the problem of dying. Results of the research lead the authors of this article to the conclusion that in the future the program of nursing care has to be extended. It should involve more lessons related to dying, not only as a subject of the nursing care, but also as a part of other university subjects.
Keywords: ankete; Attitude To Death; Ethics, Nursing; Etika zdravstvene nege; medicinska etika; Medicinska sestra-bolnik, odnosi; Nurse-Patient Relations; Odnos do smrti; Questionnaires; student; Students, Nursing; študenti; Študenti zdravstvene nege; Terminal Care; terminalni bolnik; Umirajoči, oskrba; umiranje; zdravstvena nega